Particle deposition on the saturnian satellites from ephemeral cryovolcanism on Enceladus. Issue 12 (30th June 2014) - Hirata, Naoyuki; Miyamoto, Hideaki; Showman, Adam P.
Abstract The geologically active south pole of Enceladus generates a plume of micron‐sized particles, which likely form Saturn's tenuous E‐ring extending from the orbit of Mimas to Titan. Interactions between these particles and satellites have been suggested, though only as very thin surficial phenomena. We scrutinize high‐resolution images with a newly developed numerical shape model of Helene and find that the leading hemisphere of Helene is covered by thick deposits of E‐ring particles, which occasionally collapse to form gully‐like depressions. The depths of the resultant gullies and near‐absence of small craters on the leading hemisphere indicate that the deposit is tens to hundreds of meters thick. The ages of the deposits are less than several tens of My, which coincides well with similar deposits found on Telesto and Calypso. Our findings as well as previous theoretical work collectively indicate that the cryovolcanic activity currently occurring on Enceladus is ephemeral.